Passing the (proverbial) baton: Engaging students as partners in module design - Allen, Emma (International Journal for Students as Partners, 2023)
Student-staff partnership, understood as the situation when students and staff work together on a project, contributing equally but in potentially different ways, is an innovation that is gaining traction on university campuses worldwide. This case study details my first foray into the partnership arena. I invited undergraduate students from the Schools of Law and Geography, Geology, and the Environment at Keele University to partner with me in designing a new optional module–Contemporary Issues in Environmental Law. My aim here is to provide an honest warts-and-all account of the experience, written from my perspective. I will document the positive outcomes for both the students and staff participating, of which there were many, but also some of the challenges faced. Despite these challenges, there can be no doubt that student-staff partnership is a worthwhile endeavour, and I hope others can view this as an example that can be adapted to suit their specific contexts.